The need : a novel - Phillips, Helen, 1981- (Simon & Schuster, 2019)
From LA Times Book Prize finalist and author of THE BEAUTIFUL BUREAUCRAT comes a subversive speculative thriller about a mother of two young children who, by confronting a masked intruder in her home, slips into an existential rabbit hole where she grapples with the dualities of motherhood--joy and dread, longing and suffocation--in blazing, arresting prose.